Physical Interaction of Sodium Houttuyfonate With β-1,3-Glucan Evokes Candida albicans Cell Wall Remodeling - Da, Wenyue; Shao, Jing; Li, Qianqian; Shi, Gaoxiang; Wang, Tianming; Wu, Daqiang; Wang, Changzhong (Frontiers in Microbiology, 2019)
Candida albicans is a commonly-isolated opportunistic yeast and can endanger immune-compromised human health. As increasing isolated strains present resistance to currently-used antifungals, it is necessary to develop novel antimycotics. In a previous study, sodium houttuyfonate (SH) alone or in combination with fluconazole revealed relatively strong antifungal potential against C. albicans, and the underlying mechanism might be likely to be associated with β-glucan synthesis and transportation (Pharmaceutical Biology, 2017, 55(1): 355-359.). In present experiment, we used a standard C. albicans isolate and a phr1 mutant (phr1-/-) to investigate the interaction of SH with β-glucan, one of the critical component in cell wall and biofilm matrix. We showed that lyticase was the most effective enzyme that could significantly increase the antifungal inhibition of SH at 64 µg/mL in C. albicans SC5314 but became futile in phr1-/-. Although the minimum inhibitory concentrations (MICs) of SH were comparable in the two Candida strains used, phr1-/- appeared to be more susceptible to SH compared with C. albicans SC5314 in biofilms (64 versus 512 µg/mL). The peak areas of SH decreased markedly by 71.6%, 38.2% and 62.6% in C. albicans SC5314 and by 70% and 53.2% in phr1-/- by ultra-performance liquid chromatography (UPLC) analysis after co-incubation of SH with laminarin, extracellular matrix (EM) and cell wall. The chitin appeared to not interact with SH. We further demonstrated that sub-MIC SH (8 µg/mL) was able to induce cell wall remodeling by unmasking β-1,3-glucan and chitin in both C. albicans SC5314 and phr1-/-. Based on these findings, we propose that β-1,3-glucan can block the entrance of SH through nonspecific absorption, and then the fungus senses the interaction of SH with β-1,3-glucan and exposes more β-1,3-glucan that contributes to SH blocking in turn.